Should Policy-Based Lending Still Involve Conditionality? - Koeberle, Stefan G. (World Bank, 2013)
Traditional conditionality in policy-based lending is often criticized as being ineffective, intrusive, and corrosive. Disillusionment has led to replace ex ante conditionality with ex post conditionality and to focus on ownership, selectivity, and partnership. This article reviews experiences with conditionality in the World Bank policy-based lending and explores the benefits and drawbacks of various approaches. It argues that conditionality should play a central role in policy-based lending-but cannot substitute for country ownership and good policies. Moreover an exclusive focus on conditionality based on ex ante commitments or ex post results may not be practical or useful for the Bank policy-based lending. Thus a key recommendation in to use conditionality selectively, tailred to country circumstances. Indeed, an eclectic mix of traditional and new approaches is already being used with programmatic policy-based lending offering a particularly promising way to reconcile the debate between the traditional ex ante approach and the aspirations of a results-based approach to conditionality.